Sistem Presidensial Melalui Penerapan Ambang Batas Parlemen (Parliamentary Threshold) Dalam Pemilihan Umum 2024 Di Indonesia - Isnaini, Laylia; Wahyudi, Eko (Legal Spirit, 2025)
In writing this thesis, the author intends to evaluate the strengthening of the presidential system through the implementation of the parliamentary threshold in general elections in Indonesia. The type of research used is normative juridical legal research with a statutory approach to the issues raised by the author. The application of regulations regarding the parliamentary threshold as a strengthening of the presidential system in general elections in Indonesia raises the pros and cons because there are positive and negative sides generated from the application of the parliamentary threshold. From the existence of two different views, the author in this thesis wants to evaluate the comparison before the use of the parliamentary threshold in general elections in Indonesia and after the application of the parliamentary threshold in general elections in Indonesia. The result of this research is that the evolution of the political system reflects efforts to achieve a balance between political stability and inclusive representation. Despite some criticisms regarding the lack of flexibility and the potential for fragmentation, Indonesia's political system continues to evolve and adjust to meet the demands of a maturing democracy.